Management difficulties in a patient with obsessive-compulsive personality disorder: attention on therapeutic relationship (Bangladesh Journal of Psychiatry, 2021)
Despite high estimated prevalence, clinical recognition of obsessive-compulsive personality disorder is comparably lower. Multiple treatment options are available but very few data are present supporting their reliability. A case of obsessive-compulsive personality disorder was illustrated here. Diagnosis was made as he was perfectionist, over-conscientious and inflexible about morality, ethics and values, unable to delegate tasks with others, rigid and significantly functionally impaired. Along with pharmacological treatments, psychological interventions including cognitive behavioral therapy, problem solving counselling and family counselling were exercised where an effective therapeutic relationship with the patient was emphasized. Noticeable improvement was achieved thereafter. Further research is necessary regarding the management of the disorder.Bang J Psychiatry 2021;35(2): 36-38